I servizi psichiatrici fra scienza e politica - Filippi, Andrea (Il sogno della farfalla, 2020)
1978 represents a fundamental year in Italian history. Many reforms were established as a result of a social, cultural and political upheaval which had been investing the whole country since after the end of the second World War. These reforms included: law 194 on women's health, the establishment of the National Health Service and law 180 on public psychiatric assistance. Although the latter two originated from the same political and cultural roots, they show significant differences in terms of ideological and scientific background. The former realized an integration between medical science, social political practices and citizens health protection. By doing so preventive and therapeutic aspects were reconciled. The latter is instead the result of a clear idealization of socialcultural factors at the expense of medical scientific research in the psychiatric field. This article analyzes the factors that have determined a progressive demedicalization in psychiatry contributing to the current crisis of the mental health service.